Factors influencing subjective walkability: Results from built environment audit data - Lancelot Rodrigue; Julie Daley; Léa Ravensbergen; Kevin Manaugh; Rania Wasfi; Gregory Butler; Ahmed El-Geneidy (Journal of Transport and Land Use)
Subjective walkability is a measure of the perceived friendliness of walking in an area. Though subjective walkability is less commonly assessed than objective measurements, the latter often fail to reflect the experience of walking. This study aims to better understand subjective walkability and how it varies between travel and leisure walking by investigating its relationship with the built environment and land-use characteristics. Data is collected from 848 street segments in Montreal, Canada, using the MAPS-mini audit tool, external measurements including Walkscore as well as synthetic subjective walkability scores. Mixed effect multilevel models are then generated using travel and leisure subjective walkability scores as dependent variables and built environment features as independent variables. Statistically significant positive predictors of perceived walkability differ between walking for travel and walking for leisure. Walkscore is found to have a weak but significant effect on perceived walkability for travel but no effect at all for leisure. Based on this research, a multi-scalar approach both at the street and neighborhood level making use of a combination of objective and subjective walkability measures should be employed to study predictors of walking behavior. Lastly, distinctions of walking behaviors based on trip purpose should be integrated in future research.